Branding Grenlandii formą ekspresji tożsamości narodowej? - Dominika Bartnik-Światek (Sprawy Narodowościowe, 2016)
Branding Greenland as a form of expression of national identity? In the times of globalisation there is a tendency for countries to differentiate from others. More and more governments decide to launch professional nation branding campaigns in order to communicate to a broad public what a particular country has to offer as well as what values and images it wants to be associated with. Greenland is an example of a country that after a long period of colonisation and establishing self-government, in 2009 began to redefine its identity and reveal it to the world. A branding campaign has been implemented to communicate a newly defined image of Greenland. This campaign has been carried out using mainly social media and the tools that the Internet has to offer. The aim of this paper is to explore the concept of nation branding and to define the relation between nation branding and national identity. The purpose is also to analyse what images of Greenland as a brand are presented by “Pioneering nation” campaign. Branding Grenlandii formą ekspresji tożsamości narodowej? W czasach globalizacji poszczególne państwa starają się wyróżnić na tle innych państw. Coraz więcej rządów decyduje się na przeprowadzenie profesjonalnych kampanii brandingowych, po to by podkreślić swoją wyjątkowość oraz to, że mają dużo do zaoferowania. Grenlandia to przykład państwa, które po długim okresie skolonizowania i po uzyskaniu autonomii w 2009 roku, zaczęło na nowo definiować swoją tożsamość i komunikować ją światu. W tym celu wdrożona została kampania, która wykorzystywała głównie media społecznościowe oraz inne narzędzia, które zapewnia internet. Celem niniejszego artykułu jest zbadanie zależności między brandingiem narodowym a tożsamością narodową, jak też analiza obrazu Grenlandii jako marki konstruowanej w kampanii „Pioneering nation”.